The Behavioral Intention to Adopt XBRL In the Accounting Firms: Tunisian Context - Helmi Hentati; Manel Borchani Maktouf; Neila Boulila Taktak (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - What are the factors that influence the intention of Tunisian accounting firms to adopt the "XBRL" accounting information system? Motivation - The low level of awareness about XBRL adoption especially in developing countries and the latest developments of this information system in favor of Artificial Intelligence which should be considered as a motivational tool for adoption. Idea - the choice to adopt an innovation depends on several factors. This study uses the technology acceptance model theory to examine intentions in order to explore the factors influencing adoption of XBRL technology. Data - The survey data was collected by means of a self-administered questionnaire sent to accounting firms. Tools - Logistic regression, which allowed us to test the influence of each factor in three categories: technical, organizational and environmental on the behavioral intention to adopt XBRL. Findings - Perceived benefits and a qualified staff among the main motivating factors for XBRL adoption as well as mimetic and normative pressure can be a source of reinforcing adoption intentions. However, the communication factor is suggested as an unexpected demotivating factor for XBRL adoption. Contribution - we have two contributions: the first one managerial for regulatory authorities or business owners in order to encourage the intentions of the adoption of this accounting information system and other similar technologies. The second contribution to the previous literature since we have used new data collected from Tunisian companies and present new results in a developing country context.
Keywords: M49; 650; XBRL; Behavioral intention; TOE; Tunisian context